Acute decompensated heart failure in a patient with primary aldosteronism successfully treated with an adrenalectomy: A case report. Issue 3 (March 2022) - Imamura, Yasutaka; Suzuki, Atsushi; Nomoto, Michiru; Takano, Mayu; Sawa, Shintaro; Hoki, Ryogo; Kikuchi, Noriko; Yoshida, Yusaku; Uto, Kenta; Niinami, Hiroshi; Hagiwara, Nobuhisa
Abstract: Primary aldosteronism is often associated with heart failure (HF), and is reportedly difficult to treat in some cases. We report a case of severe HF associated with primary aldosteronism. A patient with HF, who was suspected of having primary aldosteronism, was referred to and examined at our hospital. After detailed examination, the patient was diagnosed with exacerbation of HF, and was treated at our department. Catheterization after admission revealed Forrester class IV HF. The patient was treated with catecholamine infusion in combination with medical treatment including mineralocorticoid receptor antagonists. The patient was diagnosed with hypertension due to primary aldosteronism and intractable secondary HF with increased peripheral vascular resistance. An open adrenalectomy was successfully performed under intra-aortic balloon pumping. Right heart catheterization, performed soon thereafter, demonstrated improvement in the patient's blood pressure and hemodynamics. We speculate that the improved cardiac function resulted from a reduction in the vascular resistance, as a consequence of the adrenalectomy. <Learning objective: Acute decompensated heart failure (HF) is one of the cardiovascular complications in patients with primary aldosteronism. However, there are few reports on the effective management of severe HF with concomitant primary aldosteronism. Although the appropriate time-frame for performing adrenalectomy remains undetermined, the procedure may effectively improve hemodynamics of patients with primary aldosteronism; this facilitates treatment of severe HF.>